Ultra-Mini-Percutaneous Nephrolithotomy for the Treatment of Upper Urinary Tract Stones Sized between 10-20 mm in Children Younger Than 8 Years Old - Sofimajidpour, Heshmatollah; Rasouli, Mohammad Aziz; Zarei, Bushra; Hosseini, Masoumeh (Urology Journal, 2020)
Purpose: With the invention of miniature devices, it has been advised to apply less aggressive methods for the management of upper urinary tract stones, especially in children. In the recent years, ultra-mini percutaneous nephrolithotomy (UMP) has been used for the treatment of upper urinary tract stones in order to perform surgeries with less complications and more acceptable outcomes. Results reported from different medical centers have been promising. Materials and Methods: Twenty-two children aged less than 8 years old with upper urinary stones sized between 10-20 mm underwent UMP. Inclusion criteria was solitary unilateral kidney stone, stone size between 10-20 mm, normal renal function tests, absence of any congenital malformations, and history of previous ESWL failure. Data including age, sex, side of kidney involvement, size of stone, location of stone, duration of surgery, duration of hospitalization, stone composition, need for blood transfusion, damage to adjacent organs, postoperative fever, septicemia after surgery, need for narcotics, further need for a complementary method, stone-free rate, pre and post-operative hemoglobin levels, and urinary leakage from the access tract were extracted from patients’ medical files and were recorded. Results: The mean age (± standard deviation) of children was 5.22 (±1.57) years. Fourteen (63.6%) patients were male. Fifteen (68.2%) renal stones were located in the right kidney, and 82% of patients had pelvis stones. 13 (59%) patients’ stones were composed of calcium oxalate. Stone-free rate was 95.5%. In none of the cases urinary leakage, septicemia after surgery, injury to adjacent organs, and need for blood transfusions was reported. Conclusion: Ultra-mini percutaneous nephrolithotomy is an efficient and safe method for treating urinary stones sized between 10-20 mm in children.